Effect of Electroacupuncture Stimulation on Brown Adipose Tissue Thermogenesis - Ting Li; Meng Wu; Junjian Tian; Yitong Li; Zhigang Li (Medical Association of Pharmacopuncture Institute, 2024)
Background : Brown adipose tissue (BAT) is a unique thermogenic tissue in mammals mediated by uncoupling protein 1 (UCP1). The energy generated by glucose and triglyceride metabolism is released and transmitted throughout the body as heat. Understanding the factors influencing BAT function is crucial to determine its metabolic significance and effects on overall health. Although studies have shown that electroacupuncture (EA) at specific acupoints (e.g., ST36) can stimulate BAT, its effects at other acupoints are not well understood. Further research is needed to investigate the potential effects of EA at these acupoints and their association with BAT activation. Objectives: This study aimed to investigate the effects of EA at the GV20 and EX-HN3 acupoints. Specifically, the effects of EA on BAT thermogenesis were analyzed by infrared thermography, western blotting, and real-time polymerase chain reaction (PCR). Methods : A total of 12 C57BL/6J mice were randomly divided into the EA and control groups. The EA group received EA at GV20 and EX-HN3 for 20 min once daily for 14 days. The control group underwent the same procedure but without EA. The core body temperature was monitored. Infrared thermal images of the back of each mouse in both groups were captured. BAT samples were collected after euthanasia to analyze UCP1 protein and UCP1 mRNA. Results : The average skin temperature in the scapular region of the EA group was increased by 1.1℃ compared with that of the C group (p < 0.05). Additionally, the average temperature along the governor vessel in the EA group was increased by 1.6℃ (p = 0.045). EA significantly increased the expression of UCP1 protein (p = 0.001) and UCP1 mRNA (p = 0.002) in BAT, suggesting a potential link between EA and BAT thermogenesis. Conclusion : EA induced BAT thermogenesis, suggesting GV20 and EX-HN3 as potential acupoints for BAT stimulation. The experimental results also highlighted unique meridian characteristics as demonstrated by elevated skin temperature along the governor vessel in mice.